Penggunaan Artificial Intelligence (AI) Terhadap Transformasi Pembelajaran Dalam Dunia Pendidikan - Regina Amina Mene; Febrianus Aquino Mboi; Alexandro S. Triyanto (FKIP UNSULTRA, 2026)
The development of artificial intelligence (AI) in the digital era has significantly transformed learning and thinking patterns in education. This study aims to analyze the influence of AI on learning transformation, critical thinking skills, and the challenges of its implementation in higher education. The research employed a qualitative method using a literature review approach, supported by simple interviews to obtain data related to experiences in using AI during the learning process. Data were collected from journals, scientific articles, and relevant literature sources, then analyzed descriptively. The findings indicate that AI plays an important role in improving learning effectiveness through easier access to information, personalized learning, academic task assistance, and the development of analytical and problem-solving skills. AI also encourages a shift from conventional learning methods toward more independent, flexible, and interactive digital learning. However, excessive dependence on AI may reduce students’ critical thinking abilities, creativity, and independent understanding of learning materials.Therefore, the use of AI must be accompanied by critical awareness, digital literacy, and proper supervision so that AI functions as a supporting tool rather than replacing human intellectual abilities. This study recommends the development of ethical and balanced educational policies to optimize AI utilization while maintaining the quality of learning and supporting students’ intellectual development.